2023
DOI: 10.3389/fonc.2022.1068778
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties of bromelain: State-of-the-art and recent trends

Abstract: Bromelain is a key enzyme found in pineapple (Ananas comosus (L.) Merr.); a proteolytic substance with multiple beneficial effects for human health such as anti-inflammatory, immunomodulatory, antioxidant and anticarcinogenic, traditionally used in many countries for its potential therapeutic value. The aim of this updated and comprehensive review focuses on the potential anticancer benefits of bromelain, analyzing the cytotoxic, apoptotic, necrotic, autophagic, immunomodulating, and anti-inflammatory effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 140 publications
0
9
0
Order By: Relevance
“…MAPK mitogen-activated protein kinase (MAPK) pathway is vital for the adaptation of the cell to stress and its activation is highly involved in the inflammation process ( Motyka et al, 2023 ; Prasher et al, 2023 ). The cell inflammation induction by lipopolysaccharide (LPS) triggers a series of signaling pathways including MAPK and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) ( Li et al, 2016 ; Capó et al, 2021 ; Pezzani et al, 2023 ). MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…MAPK mitogen-activated protein kinase (MAPK) pathway is vital for the adaptation of the cell to stress and its activation is highly involved in the inflammation process ( Motyka et al, 2023 ; Prasher et al, 2023 ). The cell inflammation induction by lipopolysaccharide (LPS) triggers a series of signaling pathways including MAPK and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) ( Li et al, 2016 ; Capó et al, 2021 ; Pezzani et al, 2023 ). MAPKs are involved in the phosphorylation of JNK, ERK and p38 which regulate the expression of MSK 1/2 and then p65 ( Xie et al, 2019 ; Garzoli et al, 2022 ; Li et al, 2023 ).…”
Section: Anticancer Mechanisms and Targeting Signaling Pathways By Al...mentioning
confidence: 99%
“…Additionally, bromelain had been shown to reduce the risk of blood clot formation by reducing platelet aggregation and decreasing the levels of certain clotting factors in the blood. 67 Lotz-Winter was one of the first researchers to study the role of fibrin synthesis in blood clotting. 68 It has been revealed that bromelain could increase the inhibition time of prothrombin, which could lead to the presence of inactive prothrombin in the blood, thereby reducing the time required for blood coagulation.…”
Section: Fibrinolysismentioning
confidence: 99%
“…Cancer occurs as a result of somatic mutations in the cells that make up tissues [128][129][130]. Random mutations that constantly accumulate without having a negative impact on cell survival are passenger mutations and they do not cause clonal expansion of a malignant transformed cell, they do not promote tumour growth instead driver mutations cause oncogenesis [131,132]. P. emodi plays a very important role in anti-mutagenic activity.…”
Section: Anti-mutagenicmentioning
confidence: 99%